Role of Interfacial Oxide Layer in MoOx/n-Si Heterojunction Solar Cells - X. M. Song; Z. G. Huang; M. Gao; D. Y. Chen; Z. Fan; Z. Q. Ma (International Journal of Photoenergy)
Interfacial oxide layer plays a crucial role in a MoOx/n-Si heterojunction (MSHJ) solar cell; however, the nature of this interfacial layer is not yet clarified. In this study, based on the experimental results, we theoretically analyzed the role of the interfacial oxide layer in the charge carrier transport of the MSHJ device. The interfacial oxide layer is regarded as two layers: a quasi p-type semiconductor interfacial oxide layer (SiOx(Mo))1 in which numerous negatively charged centers existed due to oxygen vacancies and molybdenum–ion-correlated ternary hybrids and a buffer layer (SiOx(Mo))2 in which the quantity of Si-O bonds was dominated by relatively good passivation. The thickness of (SiOx(Mo))1 and the thickness of (SiOx(Mo))2 were about 2.0 nm and 1.5 nm, respectively. The simulation results revealed that the quasi p-type layer behaved as a semiconductor material with a wide band gap of 2.30 eV, facilitating the transport of holes for negatively charged centers. Additionally, the buffer layer with an optical band gap of 1.90 eV played a crucial role in passivation in the MoOx/n-Si devices. Furthermore, the negative charge centers in the interfacial layer had dual functions in both the field passivation and the tunneling processes. Combined with the experimental results, our model clarifies the interfacial physics and the mechanism of carrier transport for an MSHJ solar cell and provides an effective way to the high efficiency of MSHJ solar cells.